2019
DOI: 10.12681/mms.20363
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis and new records of the invasive polychaete Boccardia proboscidea (Annelida: Spionidae)

Abstract: The spionid polychaete Boccardia proboscidea Hartman, 1940 is a tube-dweller and shell/stone-borer widely occurring in temperate waters across the world and considered invasive in many areas. It was originally described from California, USA, and later reported from Pacific Canada, the Asian Pacific, Australia, New Zealand, Argentina, South Africa, and northern Europe. The Bayesian inference analysis of sequence data of three gene fragments (836 bp in total) of the mitochondrial 16S rDNA, nuclear 28S rDNA, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Simon et al (2019) for the first time successfully used methylene green staining to delineate species of Pseudopolydora. They showed that staining patterns anterior to chaetiger 6 supported the division of the examined specimens into five species, although "all species had similar patterns in dorsal staining posterior to chaetiger 6" (Simon et al 2019: 19).…”
Section: Branchial Distributionmentioning
confidence: 99%
“…Simon et al (2019) for the first time successfully used methylene green staining to delineate species of Pseudopolydora. They showed that staining patterns anterior to chaetiger 6 supported the division of the examined specimens into five species, although "all species had similar patterns in dorsal staining posterior to chaetiger 6" (Simon et al 2019: 19).…”
Section: Branchial Distributionmentioning
confidence: 99%
“…B. proboscidea has become a pest to abalone farms in South Africa since 2004 when it was first observed burrowing into cultured abalone (Simon et al., 2009). The introduced B. proboscidea presumably originated from the North American Pacific Coast where it is found in the wild benthos (Hartman, 1940, 1941; Jaubet et al., 2018; Simon et al., 2009), although the species is now widely distributed throughout the world (Canada, Australia, New Zealand, Argentina, South Africa, Asia, and Europe) (Radashevsky et al., 2019). The presumed origins of introduced mud worms are, however, often based on circumstantial evidence such as documented movement of shellfish stock and the first described locations of mud worm infestations.…”
Section: Mud Worm Introduction Via Shellfish Translocationmentioning
confidence: 99%
“…they inhabit both fresh and marine waters with silty, sandy and rocky bottoms, from shallow to deep waters, and from clean to polluted environments (blake et al 2017(blake et al , Martinez & adarraga 2019. In the bay of biscay and Mediterranean waters, new species are regularly recorded as progress is made in the systematics and biogeography of Spionidae (aguirrezabalaga & Ceberio 2005;Meißner 2005; Çinar et al 2015;lavesque et al 2015;radashevsky et al 2016;Surugiu 2016;bogantes et al 2018;Delgado-blas et al 2018;Delgado-blas et al 2019;radashevsky et al 2019).…”
Section: Introductionmentioning
confidence: 99%